Establishing Porcine Monocyte-Derived Macrophage and Dendritic Cell Systems for Studying the Interaction with PRRSV-1 - Singleton, Helen; Graham, Simon P.; Bodman-Smith, Katherine B.; Frossard, Jean-Pierre; Steinbach, Falko (Frontiers in Microbiology, 2016)
Monocyte-derived macrophages (MoMØ) and monocyte-derived dendritic cells (MoDC) are two model systems well established in human and rodent systems that can be used to study the interaction of pathogens with host cells. Porcine reproductive and respiratory syndrome virus (PRRSV) is known to infect myeloid cells, such as macrophages (MØ) and dendritic cells (DC). Therefore, this study aimed to establish systems for the differentiation and characterization of MoMØ and MoDC for subsequent infection with PRRSV-1. M-CSF differentiated monocyte-derived macrophages (MoMØ) were stimulated with activators for classical (M1) or alternative (M2) activation. GM-CSF and IL-4 generated monocyte-derived dendritic cells (MoDC) were activated with the well established maturation cocktail containing PAMPs and cytokines. In addition, MoMØ and MoDC were treated with dexamethasone and IL-10, which are known immuno-suppressive reagents. Cells were characterized by morphology, phenotype and function and porcine MØ subsets highlighted some divergence from described human counterparts, while MoDC, appeared more similar to mouse and human DCs. The infection with PRRSV-1 strain Lena demonstrated different replication kinetics between MoMØ and MoDC and within subsets of each cell type. While MoMØ susceptibility was significantly increased by dexamethasone and IL-10 with an accompanying increase in CD163/CD169 expression, MoDC supported only a minimal replication of PRRSV These findings underline the high variability in the susceptibility of porcine myeloid cells towards PRRSV-1 infection.